A Comparative Study of the Drill-and-Practice Method and the Problem-Based Learning (PBL) Method in Terms of Students' Mathematical Disposition Abilities in the Basic Statistics Course - Indra Kurniawan; Iim Marfu'ah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
The Drill and Practice Method and the Problem-Based Learning (PBL) Method are effective learning methods used in classroom instruction. This study employs a Static Group Comparison design to analyze the differences in effectiveness between the Drill and Practice Method and the Problem-Based Learning (PBL) Method in enhancing students' mathematical disposition abilities in the basic statistics course. The research design used is quasi-experimental. The research design is static group comparison. The groups were divided into two, one as the experimental group and the other as the control group. The population of this study consists of third-semester students at Universitas Indraprasta PGRI Jakarta. The sample for the study was taken using area or cluster sampling, as the sample was taken based on the location of the sample area. Therefore, the sample size was 41 students for the experimental group and 36 students for the control group. The results of the study indicate that the significance value (Sig.) for all sources (Method, Disposition, and Method * Disposition interaction) is 0.000, which is less than 0.05. This indicates that there is a significant difference between the average groups. In other words, the Method, Disposition, and their interaction have a significant effect on the dependent variable. Further analysis shows that the Drill and Practice method is better applied than PBL because all respondents prefer practicing and are not yet comfortable with solving problems.